Global sport marketing contemporary issues and practice - Desbordes, Michel; Richelieu, André (Routledge research in sport business and management, 2014)
This study of contemporary sports marketing examines the opportunities and threats posed by a global sports market, outlining the tools and strategies that marketers and managers can use to take advantage of those opportunities.